BİR KUŞAK-BİR YOL PROJESİ KAPSAMINDA AKDENİZ TİCARET LİMANLARINDA TÜRKİYE FIRSATLARI - Zeki Yılmaz; Betül SABANCI (Ekonomi Maliye İşletme Dergisi, 2021)
Silk Road; It has witnessed the intercontinental exchange of many products in history, keeping the trade alive and shaping the economy. China, which produces less costly thanks to its cheap and qualified workforce, has started to seek new markets in the global economy. For this purpose, The Chinese Government, seeking new trade routes, initiated the modernized design of the historical Silk Road in 2013, when the president announced the modernized design of the Historical Silk Road. The New Silk Road Project has been built with three separate centers, namely highway, seaway and railway. In the study, maritime trade and the comparison of Piraeus Port and Izmir Çandarlı and Mersin ports were made on this line. In the study, it was tried to reveal the economic advantages that our country, which is in the first place in the world with its geographical location, qualified workforce advantages and port capacities, can benefit if the investment and trade opportunities offered by the project are turned into opportunities.